PENGARUH ASPEK KERENTANAN USAHA PETERNAKAN DOMBA TERHADAP PEMBANGUNAN PETERNAKAN BERKELANJUTAN - Mochammad Husnul Yaqin; Amam Amam; Supardi Rusdiana; Agus Sholehul Huda (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
Indonesian society has a dependence on the livestock sector, because livestock can meet the needs of animal protein needed by humans as a food source, therefore the livestock sector is very important for human survival. The novelty of the research is to find aspects of the vulnerability of sheep farming business partnerships to sustainable livestock development. The research was conducted at Gumukmas Multi Farm (GMF) Jember District. The research method is descriptive and causal. The research variables consisted of the vulnerability aspects of the sheep  farming partnership business (X) and 5 (five) dimensions of sustainable livestock development consisting of the ecological dimension (Y1), the economical dimension (Y2), the social and cultural dimension (Y3), the institutional dimension (Y4), and the technological dimension (Y5). The results showed that the vulnerability aspect of the sheep farming partnership business had a negative and significant effect on the ecological, economical, social and cultural dimensions, and technological. The conclusion of the study shows that the vulnerability aspect of the sheep farming partnership business should be a concern for farmers and GMF because it has a bad impact on sustainable livestock development.